Increased incidence of immune thrombocytopenia (ITP) in 2021 correlating with the ongoing vaccination campaign against COVID‐19 in a tertiary center – A monocentric analysis. (15th February 2023) - Schaefers, C.; Paulsen, F.‐O.; Frenzel, C.; Weisel, K.; Bokemeyer, C.; Seidel, C.
Summary: Immune thrombocytopenia (ITP) was reported as a rare complication of COVID‐19 vaccines. We conducted a retrospective single‐center analysis of all ITP cases detected in 2021 and compared the quantity with the pre‐vaccination years, from 2018 to 2020. In 2021, a two‐fold increase in ITP cases was identified compared to previous years; 11 of 40 cases (27.5%) were considered COVID‐19‐vaccine related. Our study highlights an increase in ITP cases at our institution, probably related to COVID‐19 vaccinations. Further studies are needed to investigate this finding globally.